2014
DOI: 10.1111/1755-5922.12079
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone Attenuates Atrial Structural Remodeling and Atrial Fibrillation Promotion in Alloxan‐Induced Diabetic Rabbits

Abstract: SUMMARYIntroduction: The pleiotropic effects of glitazones may favorably affect atrial remodeling. We sought to investigate the effects of peroxisome proliferator-activated receptor-c (PPARc) activator rosiglitazone on atrial structural remodeling and atrial fibrillation (AF) promotion in alloxan-induced diabetic rabbits. Methods: Twenty alloxan-induced diabetic rabbits were randomly divided into two groups (10 animals in each group), namely the diabetic rosiglitazone group (treated with rosiglitazone 2 mg/day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…We have shown that rosiglitazone attenuates atrial structural remodeling reducing the interatrial activation time and the atrial interstitial fibrosis in alloxan-induced diabetic rabbits [31].. Also, rosiglitazone treatment increased plasma antioxidant enzyme superoxide dismutase (SOD) activity and decreased oxidant stress and inflammatory markers including malondialdehyde (MDA), C-reactive protein (CRP), and TNF-α levels. [32] We have previously described two patients with diabetes who experienced a remarkable improvement in their paroxysmal AF episodes following treatment with rosiglitazone [33]. However, two large RCTs, namely RECORD [34] and PROactive [35] which enrolled high-risk patients with type 2 diabetes failed to demonstrate a significant reduction of AF risk from TZDs compared with controls.…”
Section: Thiazolidinedionesmentioning
confidence: 99%
“…We have shown that rosiglitazone attenuates atrial structural remodeling reducing the interatrial activation time and the atrial interstitial fibrosis in alloxan-induced diabetic rabbits [31].. Also, rosiglitazone treatment increased plasma antioxidant enzyme superoxide dismutase (SOD) activity and decreased oxidant stress and inflammatory markers including malondialdehyde (MDA), C-reactive protein (CRP), and TNF-α levels. [32] We have previously described two patients with diabetes who experienced a remarkable improvement in their paroxysmal AF episodes following treatment with rosiglitazone [33]. However, two large RCTs, namely RECORD [34] and PROactive [35] which enrolled high-risk patients with type 2 diabetes failed to demonstrate a significant reduction of AF risk from TZDs compared with controls.…”
Section: Thiazolidinedionesmentioning
confidence: 99%
“…Experimental studies have demonstrated that TZDs prevent atrial electrical and structural remodeling through their antiinflammatory and antioxidant properties [75][76][77][78][79]. The possible targets of PPAR-c agonists include transforming growth factor-b (TGF-b), tumor necrosis factor-a (TNF-a), atrial natriuretic peptide (ANP), superoxide dismutase (SOD), malondialdehyde (MDA), NADPH oxidase subunits, and voltage-dependent Ca 2+ currents [80].…”
Section: Upstream Therapies For Diabetes Mellitus Related Atrial Remomentioning
confidence: 99%
“…The exact underlying pathophysiological mechanisms of such remodeling processes are not fully understood [5]. In an alloxan-induced diabetic rabbit model, our group had previously demonstrated that hyperglycemic conditions lead to increased interstitial fibrosis and higher likelihood of AF development[7], as well as reduction of the Na + current ( I Na ) and increasement of the Ca 2+ current ( I CaL ) in the atria [8]. In the past, it had been demonstrated that an increase in oxidative stress leads to shortened action potential durations (APDs) in the atria due to the elevated transient outward K + current [10] and promotes Ca 2+ release from the intracellular store [11].…”
Section: Introductionmentioning
confidence: 99%